2020
DOI: 10.1007/s40962-020-00442-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Carbide-Promoting Elements on the Microstructure of High-Silicon Ductile Iron

Abstract: Because of its low cost, steel scrap is one of the most important raw materials for the production of ductile iron (DI). The amount of carbide-promoting elements in steel scrap, such as chromium, manganese, molybdenum, niobium and vanadium, is expected to increase in the future. Most of these elements have a negative impact on the microstructure and mechanical properties of DI. The solubility of carbide-promoting elements in solid solutionstrengthened DI materials, standardized in DIN EN 1563:2011, is modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…For all HSDI samples with different Nb content, a change in the phase fraction in the metallic matrix was observed, as well as the presence of small irregular particles randomly distributed and corresponding to polygonal primary NbC carbides. These particles form before the casting due to the high affinity between Nb and C atoms, so they are called primary carbides [18,21,22,[24][25][26][27][28][29][30][31]. Unlike other carbide-forming elements (Mo, Cr, and V), precipitation of NbC carbides occurs randomly throughout the material rather than by positive segregation.…”
Section: Microstructural Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…For all HSDI samples with different Nb content, a change in the phase fraction in the metallic matrix was observed, as well as the presence of small irregular particles randomly distributed and corresponding to polygonal primary NbC carbides. These particles form before the casting due to the high affinity between Nb and C atoms, so they are called primary carbides [18,21,22,[24][25][26][27][28][29][30][31]. Unlike other carbide-forming elements (Mo, Cr, and V), precipitation of NbC carbides occurs randomly throughout the material rather than by positive segregation.…”
Section: Microstructural Analysismentioning
confidence: 99%
“…A new DI classification called High-Silicon Ductile Iron (HSDI) has recently been introduced for DI with Si content ranging from 3.2 to 4.3 wt.%. It has been reported that with increasing Si content, hardness, tensile strength, and yield strength properties are promoted, while elongation to failure decreases [8,[12][13][14] and machinability and corrosion resistance improve [15][16][17][18]. These results suggest a potential advantage in the production process and performance over DI with lower Si content [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, elevated amounts of Si promote a stable eutectic solidification of carbon, resulting in higher tolerances against carbide formation, particularly in thin wall castings. 7,8 This advantageous combination of static mechanical properties and good machinability has led to a large number of casting components in a wide range of technical applications such as rotor hubs and other wind power components as well as various automotive applications like wheel suspensions and suspension arms made of high silicon ductile iron in the last years. 9 -11 However, dynamic mechanical properties of high silicon ductile iron such as the Charpy impact energy can be described as significantly disadvantageous.…”
Section: Introductionmentioning
confidence: 99%